Impact of COVID-19 pandemic and related isolation measures on violence against children in Egypt - Seham Ahmed AboKresha; Elsayed Abdelkreem; Rasha Abd Elhameed Ali (SpringerOpen, 2021)
Abstract Background Coronavirus disease 2019 (COVID-19) and related isolation measures have substantial adverse economic, social, and psychological consequences and expose children to increased risk of violence. The present study aimed to investigate the impact of the COVID-19 pandemic on violence against children in Egypt. Methods An online survey, in Arabic, was disseminated during the period from 9 to 13 April 2020, to parents of children who were up to 18 years old residing in Egypt, selected using a snowball sampling technique, during the period from 25 March to 8 April during the implementation of the nationwide compulsory isolation measures against COVID-19 (25 March to 8 April 2020). The survey covered three areas: socio-demographic data, psychological impact measured using the Impact of Event Scale-Revised (IES-R), and violence against children during the past 2 weeks measured using a modified parent-report of a child abuse screening tool (ICAST-P) developed by the International Society for the Prevention of Child Abuse and Neglect. Results Out of 1118 completed survey responses, 90.5% of children were subjected to violent discipline, 88.7% experienced psychological aggression, and 43.2% encountered severe physical punishment. Approximately 60% of respondents reported a moderate-to-severe psychological impact (IES-R scores ≥ 33), which was associated with a higher rate of violent discipline (OR: 9.3; 95% CI: 5.37-16.027; p < 0.001). Conclusions This is the first study in Egypt to provide evidence on the association of COVID-19 pandemic, its psychological impact, and increased rates of violence against children. Effective multilevel strategies are urgently required to protect children from violence and its catastrophic consequences during the continually evolving COVID-19 pandemic.